Optimal Taxation of Normal and Excess Returns to Risky Assets - Robin Boadway; Kevin Spiritus (Tinbergen Institute, 2021)
We study the optimal taxation of risk-free and excess capital income with heterogeneous rates of return, alongside an optimal nonlinear earnings tax. Households can hold three assets: one risk-free, one risky but diversifiable, and one a private investment with idiosyncratic risk whose expected return differs among households. Contrary to expectations, the optimal tax on excess returns to risky assets is ineffective for redistribution, because its effects are annulled by a Domar-Musgrave effect. It assumes only an insurance role, and is positive. The optimal tax on risk-free returns does fulfill a redistributive role, insofar the risk-free returns reveal information about the investors' types beyond what is revealed by the earnings tax base. The optimal nonlinear earnings tax takes the standard Mirrleesian form amended to take account of the stochasticity of capital income tax revenue.
Keywords: H21; H23; H24; 330; optimal capital taxation; Rate-of-Return Allowance; risk; excess returns